2020
DOI: 10.1007/s00125-020-05241-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of metabolic dysfunction in children conceived by assisted reproductive technology

Abstract: Aims/hypothesis Assisted reproductive technology (ART) is the most widely used treatment for infertility and has resulted in millions of births worldwide. The safety of the offspring has been of the utmost concern. Previous studies suggested an increase in metabolic disorders in offspring later in life. The aim of the present study was to investigate metabolic changes at age 6-10 years in offspring conceived as a result of in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI). Methods A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
1
28
0
3
Order By: Relevance
“…Our stratified analysis suggested a joint effect of PCOS/anovulatory infertility and pre-pregnancy BMI-based obesity on offspring obesity, larger than that of either exposure alone. Furthermore, our study revealed that the increased risk of offspring obesity in mothers with PCOS/anovulatory infertility was independent of fertility treatment, though it was recently reported that children born after fertility treatment were more likely to develop metabolic dysfunctions ( Cui et al , 2020 ). A recent review, summarizing epidemiological human studies and causal evidence from animal studies, indicated that long-term metabolic health in offspring was affected by intrauterine environment ( Fernandez-Twinn et al , 2019 ), which in PCOS/anovulatory infertility was characterized by excess androgen ( Rosenfield and Ehrmann, 2016 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our stratified analysis suggested a joint effect of PCOS/anovulatory infertility and pre-pregnancy BMI-based obesity on offspring obesity, larger than that of either exposure alone. Furthermore, our study revealed that the increased risk of offspring obesity in mothers with PCOS/anovulatory infertility was independent of fertility treatment, though it was recently reported that children born after fertility treatment were more likely to develop metabolic dysfunctions ( Cui et al , 2020 ). A recent review, summarizing epidemiological human studies and causal evidence from animal studies, indicated that long-term metabolic health in offspring was affected by intrauterine environment ( Fernandez-Twinn et al , 2019 ), which in PCOS/anovulatory infertility was characterized by excess androgen ( Rosenfield and Ehrmann, 2016 ).…”
Section: Discussionmentioning
confidence: 59%
“…In the general population, perinatal problems including preterm birth, large or small for gestational age (SGA) have been well established as risk factors for metabolic health ( Mericq et al , 2017 ). Also, it was recently reported that children born after fertility treatment were at increased risk of metabolic dysfunctions ( Cui et al , 2020 ). Whether a putative association of maternal PCOS with offspring obesity and/or diabetes would be modified by perinatal problems and fertility treatment, or not, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…High heterogeneity was however noted throughout the 3 glucose metabolism markers. Another recently published study [ 55 ]—of 380 children born after IVF/ICSI and 380 children born after SC, examined at the age of 6–10 years—showed significantly higher fasting blood glucose, serum insulin, and HOMA-IR levels in children born after IVF/ICSI compared to their counterparts born after SC. Thus, the findings from other studies suggest that there could be differences in glucose metabolism between children born after ART and children born after SC.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, these children were more likely to be preterm, smaller, and exhibit birth defects (Chang et al, 2020). Subsequently, such children exhibited increased fasting blood glucose, higher insulin levels, and greater HOMA-IR, but lower HDL ApoA (Cui et al, 2020). These unwanted characteristics appear to arise in mammals through alterations in development.…”
Section: Clinical and Transgenerational Implicationsmentioning
confidence: 99%